The Family Background and Cultural Landscapes of Youth in Banda Aceh: An Ethnographic Account - Bustamam Ahmad, Kamaruzzaman; Ibrahim, Fitri Zulfidar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This article examines the background of youth families in Banda Aceh and their views on issues related to radicalism in Indonesia. Studying radicalism among youth is essential to understand their thoughts on societal problems often associated with radicalism issues. There is a view that youth is the target of changes in understanding and religious and social behavior from groups that claim to be radicalized. Therefore, the understanding and perspective of youth will be beneficial to see the issue of social-religious movements in Aceh. This study is based on an ethnographic study in which the author conducted several interviews in Banda Aceh and several areas in Aceh province. In addition to conducting a bibliographical study, the authors conducted in-depth interviews to understand the informants' backgrounds. To find out their views on the issues in the radicalism movement, the author conducted an FGD with several youths. This study found three youth groups in the study of Islamic movements in Aceh: A first group is an underground group, which is not so visible among the younger generation of Muslims, but among activists of Islamic organizations and specific figures who continue to make upgrades. A second group is a group that prioritizes the power of social media and always carries out a process of religious discussion and responds to any current issues related to